2003
DOI: 10.1088/0268-1242/19/3/007
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation kinetics of AlAs and (AlGa)As layers in GaAs-based diode laser structures: comparative analysis of available experimental data

Abstract: An understanding of the kinetics of the steam oxidation of AlAs and (AlGa)As layers is crucial to maintain good control of the process of manufacturing modern GaAs-based diode microresonator vertical-cavity surface-emitting lasers (VCSELs). Mathematically, the process has been described in our previous publications. Our theoretical equations contain, however, a few adjustable parameters, which should be found experimentally. Therefore, in this paper, an extensive analysis of existing experimental results (incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Since the kinetics of the oxidation is strongly dependent on temperature but also on compositions and thicknesses of oxidized (AlGa)As layers [32], it is possible that apertures of different diameters may be produced in one oxidation process.…”
Section: Simulation Of Oxide-confined Vcselsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the kinetics of the oxidation is strongly dependent on temperature but also on compositions and thicknesses of oxidized (AlGa)As layers [32], it is possible that apertures of different diameters may be produced in one oxidation process.…”
Section: Simulation Of Oxide-confined Vcselsmentioning
confidence: 99%
“…In the SCH active region, both the carrier confinement in the thin active region and the field confinement within the wider cavity are produced independently by two (inner and outer) heterojunction pairs. By analogy, the proposed VCSEL structure shown in Figure 12 is able to independently create an active-region current-density profile and a radial optical index guiding with the aid of two different oxide apertures is called the separate-confinementoxidation (SCO) structure [32] (Figure 11).…”
Section: Simulation Of Oxide-confined Vcselsmentioning
confidence: 99%
“…However, small−aperture devices exhibit higher, both thermal and electrical resis− tances, which are followed by higher active−region tempera− ture increases leading to shorter VCSEL expected lifetime and, additionally, which limit VCSEL modulation band− width and its high−speed performance [13]. Besides, techno− logy used to obtain in a control way such small oxide aper− tures may be quite difficult because of an increasing radial oxidation rate with a decrease in a diameter of an oxide aperture [14]. Nevertheless, in applications, for which the above disadvantages are not critical, small−aperture VCSELs may be the simplest and the best solution.…”
Section: Uniform Current Injection Into Vcsel Active Regionmentioning
confidence: 99%
“…Selective oxidation is a widely used technique in the AlAs/GaAs system [12] for successful current confinement schemes in GaAs-based VCSELs [13]. Dorsaz et al reported a procedure allowing for selective anodic oxidation of lattice-matched AlInN layers and its application to the fabrication of light-emitting diodes (LEDs) [18].…”
Section: Introductionmentioning
confidence: 99%